Covert influence of politics on the lives of Jhumpa Lahiri’s characters in The Lowland - Dorji, Rinchen (International Journal of English Literature and Social Sciences (IJELS), 2019)
Many have categorized Jhumpa Lahiri’s oeuvre as the “immigrant genre”, in which the immigrants search for a location where they can feel at home in their new homeland. All her works explore this element of diaspora where there is a generational tension between immigrant parents and their children, clash of cultures, the conflicts of assimilation, and displacement in their new societies. The Lowland, to some part, deals with this usual immigrant experiences, but what sets the novel apart from all her previous works is that it has the complexity of a political novel whereby the writer uses and explores the Naxalite political movement in India as the background on which the main plot of the book drifts. Such subjects have never been covered by Lahiri before. One of the protagonists of the novel joins this movement, and its repercussion on his family members forms the core of the novel. While the writer does not delve into a political discussion of the movement itself, it forms the basis of the whole plot of the novel. It talks about how a person’s engagement in the naxalite movement affects a grueling three generations of his family after he is killed by the police. This paper shall therefore focus on the political aspect of the novel by presenting the political and personal side by side and by analyzing how politics affects the personal lives of the characters.